Experimental animal models for chronic pain [Hayvanlarda kronik aǧri modellerinin deǧerlendirilmesi] - (:unkn) unknown (My University, 2002)
Animal pain experiments have been developed primarily for the evaluation of potential analgesic drugs. For this reason most of the early studies on pain are accomplished in anesthetized animals and utilized transient stimuli to produce pain, in order to avoid tissue damage. However the animal models proliferate to study the effects of tissue and nerve injury on the development of chronic pain in the last decades. Chronic pain differs from acute pain by the nature of their persistence and by the adaptive changes. Although there are some limitations to use and to develope appropriate chronic models, this models attempt to mimic human clinical conditions. The two main goals of these models are to broaden our understanding of pain mechanism and to develop more specific therapies.
Keywords: Animal models; Chronic pain; Experimental; Neuropathic pain